Finite element analysis of composite hat-stiffened panels subjected to edge compression load - Kumar S.; Kumar R.; Mandal S. (My University, 2025)
This paper deals with optimizing smeared extensional stiffness ratio of stiffeners to that of skin of laminated composite hat-stiffened panel with the variation of pitch length stiffeners, depth of stiffeners and panel orthotropy ratio for three different plie configurations to maximize buckling capacity of the panel. Critical buckling load and global buckling mode shape of the laminated composite hat-stiffened panel are studied for the design of lightweight structures. Parametric studies of hat-stiffened panel under in-plane compressive load are presented with simply supported boundary conditions. Models are analyzed by applying Finite Element method using ABAQUS. A database is provided based on smeared stiffness approach for two different hatstiffened (600-hat-stiffened and 750-hat-stiffened) panels with variation of pitch length stiffeners, depth of stiffeners, panel orthotropy ratio and smeared extensional stiffness ratio of stiffeners to that of skin with three different plie configurations. On the basis of the study, optimum smeared extensional stiffness ratio is increased with increasing of orthotropy ratio for all similar skin, but it is also increased with decreasing extensional stiffness ratio to maximize buckling capacity of hat-stiffened panel and general guidelines are developed for the design of better hat-stiffened panel. © 2020 JUST. All Rights Reserved.